Africa. Issue 3 (4th May 2019) - Olonisakin, 'Funmi
Abstract : Go Tell the Crocodiles: Chasing Prosperity in Mozambique Rowan Moore Gerety. New York: The New Press, 2018. 26.95. 343 pp. Fighting for Peace in Somalia: A History and Analysis of the African Union Mission (AMISOM), 2007–2017 Paul D. Williams. Oxford: Oxford University Press, 2018. £70.00. 366 pp. Fighting Corruption Is Dangerous: The Story Behind the Headlines Ngozi Okonjo-Iweala. Cambridge, MA: The MIT Press, 2018. 29.95. 173 pp. Searching for Boko Haram: A History of Violence in Central Africa Scott MacEachern. Oxford: Oxford University Press, 2018. £21.99. 233 pp. Transforming Sudan: Decolonization, Economic Development, and State Formation Alden Young. Cambridge: Cambridge University Press, 2017. £75.00. 180 pp.